2019
DOI: 10.5435/jaaos-d-17-00233
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Patterns and Outcomes of Stable Hips in Infants With Ultrasonic Dysplasia

Abstract: Level II: prospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Kim et al . ( 12 ) performed a prospective cohort study in infants diagnosed with stable dysplasia. Treatment with a Pavlik harness resulted in a mean AI of 20.9° ( s.d.…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al . ( 12 ) performed a prospective cohort study in infants diagnosed with stable dysplasia. Treatment with a Pavlik harness resulted in a mean AI of 20.9° ( s.d.…”
Section: Resultsmentioning
confidence: 99%
“…2 standard deviations) around 1 year of age (mode 2: OR = 0.09; 95% CI: 0.02, 0.43; P = .002). In the second analysis, the interaction term between mode 2 and treatment (Pavlik harness Current diagnostic parameters for stable DDH only poorly correlate with outcome and cannot be used to identify hips that will have persistent or residual hip dysplasia with or without treatment (6)(7)(8)(9)(10)(11). In the context that around 80% of Graf II hips will develop to normal without treatment, there is a need to extract more data from US images to identify hips that are at risk for persistent or residual hip dysplasia at follow-up (8).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, many well-centered stable hips are currently treated with an abduction device. Therefore, it can be concluded that a large percentage of these hips might be overtreated because more than 80% would have developed to normal without treatment (6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…7 For stable hips with ultrasonic dysplasia in which the alpha angle is <55 , treatments could be observation or harness depending on physicians' decisions. 10 For Graf type IIa hip without clinical instability, the so-called 'physiological…”
Section: Discussionmentioning
confidence: 99%